FIRST DISCOVERY OF PLATINUM GROUP MINERALS IN COSTA RICA - Campos Bejarano, Lolita (2009)
We report on the presence of Platinum group minerals (PGM) discovered, for the first time, in Costa Rica. The PGM were found in small chromitite bodies of the Santa Elena ophiolite.